Meningkatkan Daya Saing UMKM di Kelurahan Pesantren Dengan Memanfaatkan Sosialisasi Pemasaran Digital - Hervian, Rendy Putra; Novanzah, Tria; Putri, Rania Ferinda Kusuma; Maulana, Catur Juinudin; Sulaksono, Prasetyo Dwi Cahyo; Andrian, Riki Dwi; Rosadi, Asyadam Abriel; Putri, Amelia Kusumaning; Sevryan, Aura; Hayu, Yuana Arshella Khoyrun Nisa; Rahma, Farikha; Adelta, Sherly Flavia; Wenda, Dhian Dwi Nur; Nugrahadini, Amalia Dyah Putri; Maftuh, Ainul (Universitas Nusantara PGRI Kediri, 2024)
In the context of digital marketing, socialization activities aim to provide understanding to business actors, especially MSMEs, about the importance of Digital Marketing and how they can use it to develop their businesses more effectively. This socialization activity was carried out in Pesantren Village, Pesantren District, Kediri City, attended by students of KKNT group 41 with participants focusing on business actors in the Pesantren village. At the observation stage, the main problem was found in 43 MSME actors, namely that business actors were not too familiar with technology broadly, which caused the reach of their product marketing to be too narrow and less able to compete with other products that had innovated. After the socialization and monitoring assistance activities, we obtained several evaluation results that became our benchmark for understanding business actors in digital marketing, including: 1) Business actors gained additional understanding of e-commerce and increased the enthusiasm of business owners to open stores in the online market, 2) MSME products in Pesantren village are increasingly known by the wider community, even outside the city of Kediri, 3) Increased turnover of business actors after the monitoring assistance activities, 4) Business actors are increasingly confident to sell their products through e-commerce so that they can compete with other products.